Tests on low ductility RC frames under high and low frequency excitations. - Quek, Ser-Tong (Earthquake engineering & structural dynamics.)
The response of low ductility reinforced concrete (RC) frames, designed typically for a non seismic region, subjected to two frequencies of base excitations is studied. Five half scaled, two bay, two storey, RC frames, each approximately 5 m wide by 3.3 m high, were subjected to both horizontal and/or vertical base excitations with a frequency of 40 Hz as well as a lower frequency of about 4 z (close to the fundamental frequency) using a shake table. The imposed acceleration amplitude ranged from 0.2 to 1.2 g. The test results showed that the response characteristics of the structures differed under high and low frequency excitations. The frames were able to sustain high frequency excitations without damage but were inadequate for low frequency excitations, even though the frames exhibited some ductility. Linear elastic time history analysis can predict reasonably well the structural response under high frequency excitations. As the frames were not designed for seismic loads, the reinforcement detailing may not have been adequate, based on the crack pattern observed. The effect of vertical excitation can cause significant additional forces inthe columns and moment reversals in the beams. The strong column, weak beam approach for lateral load RC frame design is supported by experimental observations.